Cross-Pollination Planting Plans - Stephen H. Futch; L.K. Jackson (EDIS, 2018)
The document is about addressing the issue of self-incompatibility in citrus hybrid varieties, which results in poor fruit set and compromised productivity due to inadequate cross-pollination. It explains the need for cross-pollination with compatible pollen and outlines various planting plans to enhance fruit production. The document provides detailed criteria for selecting effective pollenizer varieties and presents different planting strategies (Plans A, B, C, and D) to optimize cross-pollination in different orchard configurations, such as individual trees with space on all sides and hedgerows. It also discusses specific considerations for certain citrus varieties, emphasizing the importance of proper pollenizer placement and management to achieve better fruit yields. First published in Sept. 1993.